FRAMING ANALYSIS OF GUS ALDI'S DIGITAL DA'WAH - Soleh Arifin; Tulus Firman Prayoga; Indra Zakaria; Ida Suryani Wijaya (Journal of Research in Social Science and Humanities, 2024)
Delivering greetings and prayers to the Prophet Muhammad is a form of worship that is highly recommended in Islam. Allah SWT and His angels also sent greetings and prayers to the Prophet Muhammad, although with different intentions and ways. To expand the spread of greetings and prayers to the Prophet Muhammad, many methods of da'wah are used, such as holding prayer assemblies, lectures, and using social media as a means of da'wah. One method of da'wah through social media is through YouTube channels. One of the YouTube channels that promotes greetings and prayers to the Prophet Muhammad is Gus Aldi's YouTube channel. This YouTube channel conveys greetings and prayers in an entertaining style. The da'wah approach through humor aims to make the da'wah of greetings and prayers not boring, because it is delivered with a touch of jokes. However, it is important to remember that in Islamic teachings, not all types of jokes are allowed. . However, it is important to remember that in Islamic teachings, not all types of jokes are allowed. Some types of jokes can even be considered inappropriate or violate religious principles. In examining the phenomenon of da'wah with the prank shalawat method on Gus Aldi's YouTube channel, the author can explain more deeply about this. The methods applied in this research are: 1) Descriptive qualitative research; 2) Type of virtual ethnography research; 3) The object of research used is Gus Aldi's YouTube channel; 4) The data source taken is the shalawat prank on Gus Aldi's channel; 5) Observation and documentation data collection tools; and 6) Data analysis using content analysis. The results of this study are as follows: Prank shalawat on Gus Aldi's YouTube channel can be considered as one of the da'wah methods used to spread salawat to the Prophet Muhammad. In this context, prank shalawat is used as a means to invite and remind YouTube channel viewers about the importance of sending shalawat to the Prophet Muhammad SAW.